Communicating Gender Mainstreaming in University Curricula: A Case Study - Stundžė, Lijana; Novelskaitė, Aurelija; Adomaitienė, Reda (Acta Paedagogica Vilnensia, 2025)
The European Commission’s Gender Equality Strategy 2020–2025 stresses the need to mainstream gender in all policy areas, including education. In Lithuania, while discussions on gender mainstreaming in general education have already been ongoing for more than a decade, in higher education, the process has been limited to the development of gender equality plans, without any clearly developed programmes, methodologies or tools. The integration of gender perspectives into the curricula in higher education aims to promote critical thinking and recognise gender inequalities, but the process is facing challenges such as lack of policy, expertise and support.This article presents a study on gender mainstreaming into university curricula conducted by a team of Lithuanian researchers in the Erasmus+ KA2 project TInGLE – Academia (Through Intersectional and Gendered Lens to Equity in Academia, https://tingleacademia.org). Integration of a gender perspective enriches the academic discourse, contributes to the diversity and quality of the learning content, and reflects the experiences of all groups in society. The paper highlights the importance and implications of gender mainstreaming in the curriculum for the learning process and analyses the challenges faced. The study aimed to determine whether and how gender perspectives are integrated into the curricula of Bachelor’s and Master’s degree programmes in social sciences at university. A content analysis of 346 curricula has shown that gender mainstreaming is practically not integrated into the curricula content, and therefore gender is invisible in the curricula.Gender mainstreaming in higher education institutions requires major changes at both institutional and individual levels. First of all, a strategy needs to be developed with measures and guidelines for integrating a gender perspective into the curriculum. Organizations must maintain a gender-sensitive culture and care about gender equality. Curricula must be open to a gender perspective, and those who deliver them must be gender-sensitive and knowledgeable about integrating a gender perspective into the content of the subjects, which is why training in this area is essential. Training on the benefits of gender equality and sharing good practice with higher education institutions in other countries would also help in the face of resistance to gender mainstreaming. It is crucial that these benefits should be understood not only by feminist academics or gender equality coordinators, but also by the whole institutional community.